Longitudinal muon spin relaxation in metals and semimetals and the Korringa law - Blundell, S; Cox, S (2001)
The longitudinal muon spin relaxation in metals and semimetals is suggestive of a form of Korringa relaxation in which the hyperfine interaction between the muons and the conduction electrons plays a dominant rôle. We give an alternative derivation of the Korringa law and show how muons may thus be used to study interactions with conduction electrons at interstitial sites. The alternative derivation links the topic to the use of implanted muons both as probes of magnetic and correlated-electron systems and as proton analogues, modelling the behaviour of hydrogen impurity in metals and semimetals.